Studi Abu Sekam Padi Sebagai Bahan Subtitusi terhadap Beton Mutu Tinggi - Halim, Zainal Arifin; Amiruddin, Aswar (Borneo Engineering : Jurnal Teknik Sipil, 2024)
Concrete is one of the preferred materials for construction due to its easy application in terms of implementation methods, execution, and maintenance. One of the developments in concrete technology today is the use of waste materials such as industrial cement waste, agricultural waste, steel industry waste, and others. One agricultural waste that is being attempted to be utilized as an additive in concrete is rice husk ash (ASP), which is organic waste from the combustion process. The objective of this research is to calculate the optimal percentage of rice husk ash as a cement substitute and to determine the compressive and tensile strength values of concrete using rice husk ash at the optimal substitution percentage. To obtain the optimal percentage of rice husk ash as a substitute, an initial test was conducted by reducing the cement portion by 5%, 10%, 15%, and 20%. The optimal percentage obtained was 5.7723%. For the results of the compressive strength test and tensile strength test of concrete with the optimal percentage of rice husk ash, the values were 32.083 MPa and 3.081 MPa, respectively.